2011
DOI: 10.1371/journal.pone.0022571
|View full text |Cite
|
Sign up to set email alerts
|

The Major Antigenic Membrane Protein of “Candidatus Phytoplasma asteris” Selectively Interacts with ATP Synthase and Actin of Leafhopper Vectors

Abstract: Phytoplasmas, uncultivable phloem-limited phytopathogenic wall-less bacteria, represent a major threat to agriculture worldwide. They are transmitted in a persistent, propagative manner by phloem-sucking Hemipteran insects. Phytoplasma membrane proteins are in direct contact with hosts and are presumably involved in determining vector specificity. Such a role has been proposed for phytoplasma transmembrane proteins encoded by circular extrachromosomal elements, at least one of which is a plasmid. Little is kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
93
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(95 citation statements)
references
References 67 publications
2
93
0
Order By: Relevance
“…However, it is still not clear which of them (ATP synthase or ATP/ADP translocase) contributes more to CLas energy. CLas could be like phytoplasmas, as it depends partly on its host for energy (17). Consequently, extracellular ATP in the gut lumen and hemocoel may also be required for CLas survival (17).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it is still not clear which of them (ATP synthase or ATP/ADP translocase) contributes more to CLas energy. CLas could be like phytoplasmas, as it depends partly on its host for energy (17). Consequently, extracellular ATP in the gut lumen and hemocoel may also be required for CLas survival (17).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, it has been shown that the antigenic membrane protein of "Candidatus Phytoplasma asteris" interacts with the ATP synthase of its leafhopper vectors (17). Because the phytoplasmas lack the ATP synthetic pathway and depend partly on their host for energy, it has been suggested that host extracellular ATP in the gut lumen and hemocoel may be required for the survival of phytoplasmas (17).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The amp transcripts were the most abundant of all the analyzed gene transcripts in all three host species, and the amp transcript levels decreased in A. thaliana and M. quadripunctulatus during the CYP infection cycle. Amp interacts specifically with the M. striifrons actin vector (10), possibly to enable phytoplasma motility (11). Indeed, amp transcript levels were stable during infection of E. variegatus, possibly implying a continuous need of the gene product to reach stable colonization of the insect body.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have also shown that phytoplasma immunodominant membrane proteins interact with vector proteins (10,11) and plant proteins (12) and are subjected to strong positive selection (13)(14)(15). Moreover, phytoplasmas can modulate their genome expression according to the infection stage and the infected host species, as suggested by microarray analysis (16) and gene expression study of pathogen transcription factors (17) and of genes lying within potential mobile units (18).…”
mentioning
confidence: 99%